2002
DOI: 10.1046/j.1365-2834.2002.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

From conflict to collaboration? Contrasts and convergence in the development of nursing and management theory (1)

Abstract: Nursing has been subject to a succession of ideologies aimed at advancing practice, however, many of these approaches have been accepted in an uncritical way. In the second paper the similarities in the development of management thought are examined and the implications this has for nursing management explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Brodwin and Bourgeois (1984) in their study of management practices, undertaken in 19 organizations, found that ‘collaborative’ and ‘cultural’ patterns served to utilize consensus building amongst the organizations’ hierarchical levels. Hewison and Stanton (2002) argue that such change is taking place and that ‘policy emphasis has shifted towards collaborative and co‐operative approaches to the provision of health care’ (p. 349). However, Long (2004), in respect of nurses working in the United States, notes that more nurses must be educationally prepared as problem solvers in order to meet the management challenges of complex health care environments.…”
Section: Discussionmentioning
confidence: 99%
“…Brodwin and Bourgeois (1984) in their study of management practices, undertaken in 19 organizations, found that ‘collaborative’ and ‘cultural’ patterns served to utilize consensus building amongst the organizations’ hierarchical levels. Hewison and Stanton (2002) argue that such change is taking place and that ‘policy emphasis has shifted towards collaborative and co‐operative approaches to the provision of health care’ (p. 349). However, Long (2004), in respect of nurses working in the United States, notes that more nurses must be educationally prepared as problem solvers in order to meet the management challenges of complex health care environments.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the lack of NM involvement in EBPI is understandable given that in the UK, the contemporary NM role has undergone significant change over recent decades. Shifting health policy and associated organizational changes have had an impact on the role (Hewison 1999; Hewison & Stanton 2002; Gifford et al 2008). Frequent changes to job titles reflect the changing spheres of influence of NMs, including an increasing emphasis on the administrative aspects of their role.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…This structure creates a mirror image of the dominant typology in general practice physicians, with Enterprising and Investigative trading places. The Social and Investigative elements are also both shared with nursing, and these two professions are thought to share a number of associated structural and procedural elements in common (Hewison & Stanton, 2003). The emphasis on Enterprising is what sets health administration apart most strongly from the other health professions (Lowman, 1991).…”
Section: Who Selects This Professionmentioning
confidence: 99%